2018
DOI: 10.1101/494393
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of subtyping approaches and the underlying drivers of microbial signatures for chronic rhinosinusitis

Abstract: 23Chronic rhinosinusitis (CRS) is a heterogeneous condition characterised by persistent sinus 24 inflammation and microbial dysbiosis. This study aimed to identify clinically relevant sub-25 groups of CRS patients based on distinct microbial signatures, with a comparison to the 26 commonly used phenotypic subgrouping approach. The underlying drivers of these distinct 27 microbial clusters were also investigated, together with associations with epithelial barrier 28 integrity. 29Sinus biopsies were collected fr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Associations have previously been identified between the microbiota and inflammatory signaling and subtypes in CRS 8,9,59‐61 . In this study, few associations were observed between microbial data and nasal polyp transcription or proteins.…”
Section: Discussionmentioning
confidence: 50%
“…Associations have previously been identified between the microbiota and inflammatory signaling and subtypes in CRS 8,9,59‐61 . In this study, few associations were observed between microbial data and nasal polyp transcription or proteins.…”
Section: Discussionmentioning
confidence: 50%
“…To understand if, and how, bacteria influence host immune processes, several groups have associated microbiota surveys with host cytokine profiling or tissue function assays. Biswas and colleagues evaluated 23 CRS subjects (8 CRSwNP, 8 CRSsNP, and 7 cystic fibrosis) and 8 controls, and found 2 subgroups of CRS patients 750 . One group was characterized by low bacterial diversity and dominance of pathogens such as Pseudomonas , Haemophilus , and Achromobacter .…”
Section: Chronic Rhinosinusitis Without Nasal Polyps (Crssnp)mentioning
confidence: 99%
“…Specific dysbiosis was described in eosinophilic inflammation and atopic subjects 32 . Therefore, it was suspected that local dysbiosis not only is disease‐specific but also depends on disease endotype 33 . However, we were not able to define distinct dysbiosis profiles in atopic subjects.…”
Section: Discussionmentioning
confidence: 80%